Embracing Change: Wheat and Wild Relatives Hybridization in Uzbekistan - Gafur, Gafurov (American Journal of Biology and Natural Sciences, 2025)
Bread plays a vital role in food security and sustenance, especially in regions such as Central Asia, where wheat is the primary crop. In Uzbekistan, wheat is central to both food sovereignty and cultural traditions, with its production and consumption continuing to grow despite challenges such as climate change, water scarcity, and environmental degradation. However, wheat cultivation faces threats from pests, diseases, and climate change, necessitating innovations in breeding and genetic resources to ensure sustainable production. Wheat breeding in the country has progressively emphasized the use of local genetic resources, especially landraces and wild relatives, to boost resilience and productivity. These varieties, which have evolved to withstand the region’s challenging conditions, offer crucial traits such as drought resistance, heat tolerance, and disease resistance – essential for adapting to climate fluctuations. Recent efforts to integrate these genetic resources into breeding programs have shown potential in improving both the quality and yield of wheat, thereby enhancing food security and nutritional sustainability. However, ensuring long-term food security in the region will still require effective land management and the responsible use of water resources.